PARENTING ACTIVITIES IN IMPROVING PARENTING PATTERNS - Nurul Novitasari; Ahmad Dzakwan Syah (Universitas Al-Hikmah Indonesia, 2023)
This research aims to describe: (1) How is the implementation of parenting activities in improving parenting patterns at RA Muslimat NU 02 Sembung, (2) How effective are parenting activities in improving parenting patterns at RA Muslimat NU 02 Sembung. This research uses a qualitative research method with a descriptive approach which is used to describe or depict events or occurrences that occur in the field during the research process. The informants in this research were: the principal, teachers, committee, and parents of RA Muslimat NU 02 Sembung. To obtain the necessary data, researchers used data collection techniques through interviews, observation and documentation. The results of the research, the implementation of parenting activities in improving parenting patterns at RA Muslimat NU 02 Sembung is divided into three stages, namely: 1) Planning the parenting activity program at RA Muslimat NU 02 which includes: socialization of family-based early childhood programs, identification of learning needs, determination place, time, preparation of activity schedule program. 2) Implementation of the parenting activity program at RA Muslimat NU 02 which is carried out by all related parties and carried out at the school, program implementation is adjusted to the predetermined schedule, time and place, materials and media used are adjusted to the activity schedule. The methods used in carrying out activities are discussion, question and answer and lecture. 3) Evaluation using observation, interviews, checklists and discussion methods and carried out two weeks after the activity is completed. The final results obtained from this research are: 1) Implementation of the parenting activity program that had been planned by the school. 2) Parents have knowledge of child development and good parenting patterns for children, children's health and nutrition, children's conditions while at school. 3) Closer relationships between the school and parents, children and the community, RA Muslimat NU 02 Sembung can be increasingly known to the wider community.